(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Kifunda CF. 2023. Effects of climate change and adaptation strategies on urban crop production in Kinondoni City, Tanzania. Asian J Agric 7: 98-107. Many countries worldwide, including Tanzania, have felt the effects of climate change on the productivity of major economic sectors, such as agriculture. This study assessed climate change’s effects on urban agriculture’s sustainability in Kinondoni City, Tanzania. Specifically, the study aimed to determine: i) the effects of climate change on crop production in Kinondoni City over the last 30 years, ii) other challenges of urban agriculture in Kinondoni City, and iii) adaptation strategies employed by smallholder farmers in sustainable urban agriculture in Kinondoni City. Data collection involves accessing temperature and rainfall data from Tanzania Meteorological Agency (TMA) headquarters and administering household questionnaires to 386 respondents who engaged in urban agriculture in Kinondoni City. Five wards of Bunju (118), Kunduchi (42), Mabwepande (102), Mzimuni (28) and Wazo (96) were involved. Focused group discussion, key informant interviews, and direct observation were also employed. Data were analyzed for temperature and rainfall variations over the last 30 years and people’s knowledge of climate change indicators. The adaptation strategies employed in sustaining crop production in the study area were also quantified. The study reveals that most smallholder farmers (>70%) are aware of the indicators of climate change, which correlate with the data obtained from TMA. Among the indicators include an increase in temperature (76%) and a decrease in rainfall (73%). Pest and diseases were ranked higher (88%) among the significant effects of climate change on urban agriculture. Land scarcity was also a significant challenge in urban agriculture. The use of pesticides and fertilizers was ranked higher (65%) among the adaptation strategies employed by smallholder farmers. It is recommended that building capacity for smallholder farmers through getting access to micro-credits at low-interest rates and government support may contribute significantly to sustainable urban agriculture in Kinondoni City. Also, farmers in Kinondoni City can adopt sustainable agriculture practices such as Soil and Water Conservation practices and the use of Drought-Resistant Crop varieties to improve their resilience to future climate risks caused by climate change.